(3QSGdI aj GdYdes - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdcQje GdPj CaGV Ydi YHGOg jfGHjY hLhOg CeG HYO aEf GdYde CaVd eG ChJjg GdEfSGf hCMd eG JaQO Hg GdYHO Edi GdQMje GdQMefs
(3BNQgG (B:s
(3agPG HYV GTGQ gPG Gdjhe GdWhjd TQM HYV gPG GdaQY Gdegjd GfJgis
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdJhMjO hGdedd hGdfMds